EFFICACY OF SALBUTAMOL DELIVERED THROUGH A METERED DOSE INHALER & SPACER IN CHILDREN WITH ACUTE EXACERBATION OF ASTHMA - Tahir, Ali Mujtaba; Akhtar, Waqas; Balooch, Salah Ud Din; Ahmed, Waqas; Samar, Ali Murtaza; Sohail, Amina (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess efficacy of salbutamol delivered through metered dose inhaler (MDI) - spacer in paediatric patients with acute exacerbation of asthma.Study Design: Prospective observational study.Place and Duration of Study: Department of Paediatrics, Pakistan Naval Ship, Shifa Hospital, Karachi-Pakistan, from Jan to Dec 2018.Methodology: Ninety Five patients aged ≥6 to ≤12 years, with acute asthma exacerbation were enrolled. Any patient with fever, clinical asthma score (CAS) >7, on home treatment with drugs delivered through nebulization or on oral steroids was excluded. Clinical asthma score recorded on presentation, followed with salbutamol via Metered Dose Inhaler & spacer at dose of 400 µgm (4 x puffs of 100 µgm). Clinical asthma score rechecked after 20 min. Response to salbutamol was then compared in relation to the presenting Clinical asthma score.Results: Out of 95 children, 45 (47.9%) were male & 50 (52.1%) female with 67.4% having positive family history for asthma. Average premedication clinical asthma score was 2.44. Sixty nine (72.9%) patients had an adequate response as they exhibited clinical asthma score of 0 or fall in score of ≥2. Patients with adequate response had average clinical asthma score of 2.07 on presentation in contrast to 3.42 with inadequate response.Conclusion: Salbutamol delivered via Metered Dose Inhaler & spacer at dose of 400 µgm is an effective medication for quick relief in children with acute exacerbation of asthma. Moreover, its administration at a point where exacerbation is not much severe steers us towards more favourable outcome.